The Effect Of Using Video Learning Media On Critical Thinking Skills On The Topisc Of Environmental Pollution - Rodatul Jannah; Pramudiyanti Pramudiyanti; Nadia Meriza (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2023)
This study aims to determine the effect of instructional video media on critical thinking skills. The population of this study were all seventh grade students at SMPN 25 Bandar Lampung. The research design used in this study is a quasi-experimental design in the form of a non-equivalent control group design. The sample in this study were students from 2 classes, namely class VII C and VII D, which were selected using cluster random sampling technique. The research instrument used a pretest-posttest research sheet. Data on the average value of pretest-posttest, n-gain as a result of increasing students' critical thinking skills were analyzed by statistical tests, namely the Mann Whitney test. The results showed that students' critical thinking skills were in the "Medium" category with n- gain in the experimental class of 0.66 and students' critical thinking skills in the "Medium" category with the n-gain value in the control class lower than the experimental class, which was 0.43. From the statement above, it can be concluded that the results of the average data analysis of students' critical thinking skills between the experimental class and the control class were significantly different. This is because video media is able to display all phenomena, especially environmental pollution that occurs in detail into its types so that it can increase students' understanding of concepts which then affect students' critical thinking skills. Thus, it is known that video media can affect critical thinking skills.Â DOI: http://dx.doi.org/10.23960/jbt.v11.i1.27236